2011
DOI: 10.1177/0363546511404139
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical in Vitro Validation of Intramedullary Cortical Button Fixation for Distal Biceps Tendon Repair

Abstract: Double intramedullary cortical button fixation provides reliable fixation strength to the bone for distal biceps tendon repair and potentially minimizes the risk of posterior interosseous nerve injury. Further, based on a 2-point-fixation, this method may offer a wider, more anatomic restoration of the distal biceps tendon to its anatomic footprint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 41 publications
6
47
2
3
Order By: Relevance
“…Previous investigations have described the standard structure of the radial tuberosity in many biomechanical studies [4,14,22]. Prior CT measurements were valuable when assessing the different loads to failure and displacement of the multiple techniques of reinsertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have described the standard structure of the radial tuberosity in many biomechanical studies [4,14,22]. Prior CT measurements were valuable when assessing the different loads to failure and displacement of the multiple techniques of reinsertion.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen unpaired cryopreserved adult radius (eight left and eight rights) were used for this study; the sample size was estimated based on historical bibliography from similar studies [14,22]. This procedure was developed in the Department of Anatomy at the Universitat de Barcelona, Spain.…”
Section: Methodsmentioning
confidence: 99%
“…They have shown that biomechanical characteristics for this repair technique are comparable or superior to suture anchor repair and bicortical button fixation, respectively [18, 30]. Buchholz et al also found no major differences between monocortical button fixation versus interference screw for subpectoral proximal biceps tenodesis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Interference screws enable good fixation, but over the long term they diminish the area of biological healing by around 50%, since the region of screw insertion may not heal, as well as possibly causing osteolysis. The technique of using interference screws in association with Endobutton ® is the method that presents greatest resistance to traction (27) , but it has the same problems as shown in using interference screws and Endobutton ® separately. Transosseous stitches (22) have demonstrated satisfactory results in our experience, although they present lower fixation strength than shown by Endobutton ® and interference screws.…”
Section: Discussionmentioning
confidence: 99%